Continuous improvement strategies : how to manage, motivate, and retain staff - Hopper, Anthony Matthew (CRC Press, 2018)
During this era of continuous improvement, healthcare organizations need to be staffed by engaged, motivated, and hard-working frontline employees. As these clinical and non-clinical personnel handle most of the important tasks in any organization and are often the people who directly interact with patients and customers, it's the job of managers to oversee and motivate their staff members. Using Lean management strategies, this easy-to-read book for leaders and managers provides useful, insightful, and innovative information to help managers engage, motivate, and retain their employees during any Lean or other continuous improvement initiative.